2004
DOI: 10.1158/1078-0432.ccr-04-1147
|View full text |Cite
|
Sign up to set email alerts
|

ZD6474, a Potent Inhibitor of Vascular Endothelial Growth Factor Signaling, Combined With Radiotherapy

Abstract: Purpose: Vascular endothelial growth factor (VEGF) plays a key role in tumor angiogenesis and acts as a radiation survival factor for endothelial cells. ZD6474 (N-(4-bromo-2-fluorophenyl)-6-methoxy-7-[(1-methylpiperidin-4-yl)methoxy]-quinazolin-4-amine) is a potent VEGF receptor 2 (KDR) tyrosine kinase inhibitor (TKI) that has additional activity versus the epidermal growth factor receptor. This study was designed to determine the efficacy of combining ZD6474 and radiotherapy in vivo.Experimental Design: The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 17 publications
0
80
1
Order By: Relevance
“…Vandetanib is a tyrosine kinase inhibitor of both VEGFR-2 and EGFR, and preclinical studies have confirmed its anti-tumour effects in a range of cancer types (Wedge et al, 2002;Ciardiello et al, 2004;Taguchi et al, 2004;Williams et al, 2004;Yano et al, 2005). Phase III clinical studies are now underway with vandetanib in non-small-cell lung cancer following promising results in phase I and II studies (Holden et al, 2005;Natale et al, 2006;Tamura et al, 2006;Heymach et al, 2007a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Vandetanib is a tyrosine kinase inhibitor of both VEGFR-2 and EGFR, and preclinical studies have confirmed its anti-tumour effects in a range of cancer types (Wedge et al, 2002;Ciardiello et al, 2004;Taguchi et al, 2004;Williams et al, 2004;Yano et al, 2005). Phase III clinical studies are now underway with vandetanib in non-small-cell lung cancer following promising results in phase I and II studies (Holden et al, 2005;Natale et al, 2006;Tamura et al, 2006;Heymach et al, 2007a, b).…”
Section: Discussionmentioning
confidence: 99%
“…One potential downside to this observation is that a substantial loss of the endothelial cell compartment has been associated with the induction of hypoxia (16,17), which could limit the effectiveness of radiotherapy in vivo. Indeed, compromised perfusion as a consequence of VEGF-inhibition during radiotherapy has been associated with suboptimal efficacy (7,8). Conversely, some studies have suggested that VEGFR-blockade can lead to a transient normalization of the vasculature, leading to a window of opportunity when perfusion, oxygenation, and consequently, radiation response may be improved (4,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…A combined treatment modality with IR and ZD6474, another dual specific inhibitor of both VEGF and EGFR signaling, has previously been tested in xenografts of nonsmall cell lung cancer and glioblastoma (30,41). These studies focused on the antiangiogenic aspect of ZD6474, demonstrating reduced perfusion in the lung cancer model and reduced expression of VEGF in the glioblastoma model.…”
Section: Discussionmentioning
confidence: 99%